Pengaruh Pendekatan Saintifik Terhadap Kemampuan Berpikir Kritis Siswa Pada Pembelajaran Pendidikan Agama Islam - Hidayah, Nur; Ismail, Ismail; Qadrianti, Laeli (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study aims to test the effect of the scientific approach on students' critical thinking skills in Islamic Religious Education learning at SMP Negeri 35 Sinjai. This study is an ex-post facto study, with a quantitative approach. The population in this study were students of grades VII 1, VII 2, VIII 1, VIII 2, IX 1, IX 2. The sample determination used the Slovin formula with a total of 93 students. The data collection methods used were questionnaires and documentation. In analyzing and proving this, validity and reliability tests, normality and linearity tests, and hypothesis tests were used using simple linear regression tests. Based on the results of the study, it was obtained a hypothesis that the significance value of 0.000 <0.05, and the t count value of 17.325> t table value of 1.986 so that H0 was rejected and Ha was accepted. So it can be concluded that the scientific approach influences students' critical thinking skills in Islamic Religious Education learning at SMP Negeri 35 Sinjai with an influence of 76.7% and is included in the strong category.